A tribute to the work of Paul Allen: A catalogue of wild and cultivated bananas - Rosales, F.; Arnaud, Elizabeth; Coto, J.; International Network for the Improvement of Banana and Plantain (1999)
This publication results from a collaboration between FHIA, Honduras and INIBAP and provides information on the tremendous work carried out by Paul Allen during the 1950's and 60's to build and characterise the Musa collection of the United Fruit Co. (now FHIA's collection). The book contains data on 337 accessions of banana collected by Dr Paul H. Allen during missions mainly in South East Asia and New Guinea in the 1960s. Information about each accession is provided in a Musalogue-type format, with one accession being described per page. The information included is based on the content of banana score cards compiled by Dr Allen. These score cards morpho-taxonomic observations and evaluation data collected on the varieties in the collection. The majority of this data was entered into a database in order to produce this monograph. As a result, a safe copy of this valuable and historical work now exists. This publication aims to make known a regional and historical « wealth ». (Out of print)